2019
DOI: 10.1021/acsabm.9b00214
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Hydrophobic Fluorinated Ethylene Propylene Offers Rapid, Robust, and Irreversible Passive Adsorption of Diagnostic Antibodies for Sensitive Optical Biosensing

Abstract: Current literature data is scarce and somehow contradictory in respect to the suitability of “nonstick” fluoropolymer surfaces for immobilization of biomolecules. We have previously shown empirically that transparent Teflon fluorinated ethylene propylene (FEP) offers rapid and sensitive optical biosensing of clinically relevant biomarkers. This study shows for the first time a comprehensive experimental analysis of passive adsorption of diagnostic IgG antibodies on actual Teflon FEP microfluidic strips. Full e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…We adapted a serotyping microplate ELISA that uses serotype-specific anti-NS1 antibody clones 46 to siphon MCF devices. Multiplex capture strips with duplicate pairs of capillaries were coated internally through passive adsorption 40 with serotype-selective capture antibodies ( Table S1 ) against DENV NS1 ( Figure 5 A). Capture of viral antigen was detected using a pan-NS1 detection antibody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adapted a serotyping microplate ELISA that uses serotype-specific anti-NS1 antibody clones 46 to siphon MCF devices. Multiplex capture strips with duplicate pairs of capillaries were coated internally through passive adsorption 40 with serotype-selective capture antibodies ( Table S1 ) against DENV NS1 ( Figure 5 A). Capture of viral antigen was detected using a pan-NS1 detection antibody.…”
Section: Resultsmentioning
confidence: 99%
“…MCF strips (47 mm long) were prepared as follows: a 1.4 m length of MCF was coated with a panel of serotype-specific capture antibodies against NS1 produced in-house ( Table S1 ) at 60 μg/mL for DENV1 and 40 μg/mL for DENV2–4 in duplicate capillaries; these concentrations were selected as sufficient to yield a stable half-monolayer of antibody on the surface of Teflon FEP microcapillaries as characterized previously. 40 A positive control capillary was coated with 1 μg/mL recombinant DENV2 NS1, and a negative capillary was filled with PBS alone. These multiplexed MCF strips were incubated at RT for 1 h, and the antibody solution replaced with 0.1 mg/mL PVOH (MW 146,000–186,000 g/mol, Sigma Aldrich, UK); the strips were coated for a further 2 h and finally blocked by filling up with 4% w/v BSA (GE Healthcare Life Sciences, UK) and incubated overnight at 4 °C before cutting into 47 mm test strips that were fitted into siphon holders.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously shown that antibody surface coverage is related to immobilized antibodies’ functionality since it interferes with their orientation and steric hindrance. 31 Therefore, we explored the impact of an antibody monolayer on the serum matrix effect, since it would favor the binding of high-affinity components—antigens. As matrix interference is usually dependent on diagnostic antibodies, 8 we have tested three different immunoassays: a direct mouse IgG/anti-mouse IgG, a sandwich human PSA, and a sandwich human IL-1β, covering a range of high-performance immunoassays.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed for the IL-1β sandwich assay, where matrix interference was fully eliminated with antibody surface coverages in the range of 40–200 μg/mL ( Figure 2 B). Based on a previous FEP adsorption study in the same MCF material, 31 it is known that these CapAb concentrations promote the formation of half of the antibody monolayer with antibodies oriented “end-on” with Fab regions in line, enhancing antigen capture in microcapillary bioassays. This agrees with findings in the literature for a thyroxin assay, where the replacement of an antibody coverage with low affinity by high affinity eliminated the matrix effect of serum samples, 36 explained by the low-affinity binding of the interfering factor(s) to the immobilized antibody.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation